No. 76 of the year 2020 On Issuing the rules and procedures of enforcing the customs system of the Suez Canal economic zone = قرار رقم 76 لسنة 2020 بإصدار قواعد وإجراءات العمل بالنظام الجمركي الخاص للمنطقة الاقتصادية لقناة السويس / ٌResolution of the genera Authority for Suez Canal Economic Zone - Egypt. ٌResolution of the genera Authority for Suez Canal Economic Zone (2025)
Resolution of the General Authority for Suez Canal Economic Zone No. 76 of the year 2020 on Issuing the rules and procedures of Enforcing the customs system of the Suez Canal Economic Zone الهيئة العامة للمنطقة الاقتصادية لقناة السويس قرار رقم 76 لسنة 2020 بإصدار قواعد وإجراءات العمل بالنظام الجمركى الخاص للمنطقة الاقتصادية لقناة السويس